Cultivating a Value for Non-Human Interests through the Convergence of Animal Welfare, Animal Rights, and Deep Ecology in Environmental Education - Helen Kopnina; Brett Cherniak (MDPI AG, 2015)
While the original objective of environmental education (EE) and education for sustainable development (ESD) acquired an awareness of the natural world and its current plight, animal welfare (AW), animal rights (AR), and deep ecology (DE) have often been absent within EE and ESD. AW and AR focus their attention on individual animals, while the DE perspective recognizes the intrinsic value of the environment. In this article, we shall discuss how the integration of these three approaches within EE/ESD can and should be improved, with particular reference to the ethical underpinnings of educational scholarship and practice. This article will argue that these three positions are well placed to enhance the democratic practices of EE/ESD through the adoption of an inclusive pluralism that embraces representation of non-human species and recognizes their interests.